Relationship between c-reactive protein and screening test results of gestational diabetes in pregnant women referred to health centers in Isfahan in 2013-2014 - Maryam Kianpour; Farzaneh Saadatmand; Mehdi Nematbakhsh; Fariba Fahami (Wolters Kluwer Medknow Publications, 2019)
Background: Gestational diabetes is the second common disorder in pregnancy period, which is detected in 24-28 weeks of gestational age through screening tests. Low-grade systematic inflammation is associated with an increased risk of type 2 diabetes. C-Reactive Protein (CRP), an acute phase protein produced by hepatocytes, may be associated with diabetes. This study aimed to investigate serum levels of CRP in women with Gestational Diabetes Mellitus (GDM) and impaired glucose tolerance test compared with control subjects. Materials and Methods: This observational longitudinal study was conducted on 176 pregnant women in Isfahan. After administration of a CRP test in these women in the first trimester, a screening test of Glucose Challenge Test (GCT) with 50-g oral glucose was conducted in 24-28 weeks of gestational age. Then, CRP levels and GCT were compared. Results: Serum CRP levels were not significantly correlated with positive GCT among the women. In GDM patients, there was not a significant correlation between CRP and BMI. Conclusions: There was no significant correlation between maternal serum CRP level and gestational diabetes. Maternal serum CRP level in the first trimester cannot predict Intolerance Glucose Test (IGT) in 26-30 weeks of gestational age.